Understanding the trade-off mechanisms of energy storage and cycle stability for hybrid electrochemical capacitors with redox additives - Jingyu Li; Bing-Ang Mei; Huihua Feng; Zhengxing Zuo; Rui Xiong (Next Energy)
Redox additives have been widely used in various electrolytes to achieve an increase in the energy density of hybrid capacitors. This study investigates the trade-off mechanism of energy density and cycle stability for electrochemical capacitors with redox additives. To do so, a 1-dimensional electrochemical model considering both electric double layer and redox actions is performed for carbon-based hybrid capacitors with electrolyte of 1 mol L−1 tetraethylammonium tetrafluoroborate/acetonitrile and redox additives hydroquinone. The results show that electrochemical capacitors with redox additives worked in either Faradaic or capacitive regimes, distinguished by the “capacitor-like” or “battery-like” potential-time curve. In addition, the energy density of the device increased with the increase in concentration of hydroquinone and the decrease in imposed current density. The temporal evolution of Coulombic efficiency and spatial average concentration of hydroquinone over cycles indicate a transition from developing state to steady state. The number of cycles required for both parameters to stabilize is identical. Finally, the Faradaic regime is favored for energy density improvement. On the other hand, highly weighted cycle stability could allow relatively higher imposed current density. The results of this study can be used to further guide the design and optimization of hybrid electrochemical systems with redox additives.